We can rewrite the rectangular equation x^2 + y^2 - 8y = 0 in polar form by substituting x = r*cos(theta) and y = r*sin(theta), where r is the radius and theta is the angle in standard position.
Thus, we have:
(r*cos(theta))^2 + (r*sin(theta))^2 - 8*sin(theta) = 0
r^2 * cos^2(theta) + r^2 * sin^2(theta) - 8 * sin(theta) = 0
r^2 * (cos^2(theta) + sin^2(theta)) - 8*sin(theta) = 0
r^2 - 8*sin(theta) = 0
Therefore, the polar equation equivalent to x^2 + y^2 - 8y = 0 is r^2 - 8*sin(theta) = 0.
Rewrite the rectangular equation x^2+y^2-8y=0 as a polar equation
1 answer